Risks of preterm birth and low Apgar score among preeclamptic women - Chiquita Febby Pragitara; Risa Etika; Lilik Herawati; Aditiawarman Aditiawarman (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: Preeclampsia has been a major problem for obstetric care in Indonesia due to risks of preterm birth and lower Apgar score. Objective: This study is to examine relationships of preeclampsia, preterm births, and Apgar Score.Methods: This used an analytic study with retrospective case-control design in Dr. Soetomo Academic Hospital. A case group was taken by total sampling from medical records of all patients who had preterm delivery in 2017, and a control group of term deliveries was taken by random sampling. Then the data were analysed by using Chi-square test and Fisher’s Exact Test.Results: There were 80 samples for each group. 63.75% of patients by age of 20-35 years were who delivered preterm birth, 40.00% had normal BMI, 40.00% were nulliparous, 92.50% did not have history of preterm labour, 50.00% had preeclampsia with severe features, and 46.25% had spontaneous vaginal delivery. Around 47.14% neonates from preeclamptic women were born at 32-<37 weeks gestation, 50.00% were born with low birth weight, 52.86% had the first minute Apgar score <7, and 72.86% had the fifth minutes Apgar score =7. The statistical analysis showed a significant relationship between the preeclampsia and the preterm birth (p<0.007; OR=2.54, 95% CI 1.34-4.83). The preeclampsia was also related to lower Apgar score at 1st minute (p<0.042; OR=2.03, 95% CI 1.07-3.85) and 5th minute (p<0.046; OR=2.42, 95% CI 1.08-5.41). Preterm neonates born from preeclamptic mothers were related to lower Apgar score at 1st minute (p<0.002; OR=5.82, 95% CI 1.99-17.02) and 5th minute (p<0.001; OR 17.31, 95% CI 2.15-139.54).Conclusion: Preeclampsia could make pregnant women at risks of delivering preterm birth and neonates with low Apgar score.